Beyond Evidence-Based Belief Formation: How Normative Ideas Have Constrained Conceptual Change Research - Ohlsson, Stellan (Frontline Learning Research, 2013)
The cognitive sciences, including psychology and education, have their roots in antiquity. In the historically early disciplines like logic and philosophy, the purpose of inquiry was normative. Logic sought to formalize valid inferences, and the various branches of philosophy sought to identify true and certain knowledge. Normative principles are irrelevant for descriptive, empirical sciences like psychology. Normative concepts have nevertheless strongly influenced cognitive research in general and conceptual change research in particular. Studies of conceptual change often ask why students do not abandon their misconceptions when presented with falsifying evidence. But there is little reason to believe that people evolved to conform to normative principles of belief management and conceptual change. When we put the normative traditions aside, we can consider a broader range of hypotheses about conceptual change. As an illustration, the pragmatist focus on action and habits is articulated into a psychological theory that claims that cognitive utility, not the probability of truth, is the key variable that determines belief revision and conceptual change.